Breast Metastasis in Esophagus Cancer: Literature Review and Report on a Case - Abdulaziz Ghibour; Osama Shaheen (Case Reports in Surgery)
Esophagus cancer metastases often involve locoregional lymph nodes, lung, bone, liver, and brain. Metastatic involvement of the breast from esophagus cancer is uncommon, but if it happened, it usually presents as a part of multiple organ distal metastases. Here we report a case of the largest metastatic esophagus cancer of the breast and the chest wall, and we review the similar reported cases.